The Food-Energy Nexus is Closer to our Heart than we might think - Drechsel, Pay (2017)
Reflecting on the food-energy nexus, my first thought went to the Haber–Bosch process. Perhaps no other human invention has had a more dramatic impact on our wellbeing and mother Earth than the Haber-Bosch chemistry. As the reader might know, and I am citing here largely from Wikipedia, the Haber-Bosch process is the main industrial procedure for the production of ammonia fertiliser today. It is named after its inventors, the German chemists Fritz Haber and Carl Bosch, who developed it in the first half of the 20th century.